Remain in Naoshima : Naoshima Contemporary Art Museum. - Akimoto, Yuji; Fukutake, Soichiro; Kasahara, Ryoji (Naoshima : Benesse House Naoshima Contemporary Art Museum, 2000)
Ando, Tadao ; Appel, Karel ; Bartlett, Jennifer ; Basquiat, Jean Michel ; Borofsky, Jonathan ; Cai Guo-Qiang ; Calder, Alexander ; Francis, Sam ; Graham, Dan ; Hockney, David ; Johns, Jasper ; Judd, Donald ; Katase, Kazuo ; Kounellis, Jannis ; Kusama Yayoi ; Long, Richard ; Miyajima, Tatsuo ; Nauman, Bruce ; Nevelson, Louise ; Ohtake, Shinro ; Pollock, Jackson ; Rickey, George ; Roeth, Winston ; Stella, Frank ; Sugimoto Hiroshi ; Tremlett, David ; Turrell, James ; Twombly, Cy ; Yanagi, Yukinori ; Yasuda, Kan
biografie
Engels & Japans
boek